Student Attitudes Towards the Professional Competence of Guidance Counselors at SMA Negeri 17 Medan - Sri Rezeki Pangaribuan; Erwita Ika Violina (Insight: Journal of Counseling and Psychology, 2026)
This study aims to describe students' attitudes toward the professional competence of guidance counselors at SMA Negeri 17 Medan. The approach used in this study is quantitative descriptive. The population in this study consisted of 861 students in grades X, XI, and XII, and 262 students were sampled using stratified random sampling. The data collection method used instruments of Strongly Agree (SS), Agree (S), Disagree (TS), and Strongly Disagree (STS) based on the Likert scale. The data analysis used was descriptive percentage analysis. The results of the study on students' attitudes towards the professional competence of guidance counselors show that the average attitude of students towards the professional competence of guidance counselors at SMA Negeri 17 Medan is in the positive category. Students' attitudes towards the professional competence of guidance counselors are divided into five aspects, namely acceptance, response, assessment, organization, and characterization. The aspect of organization, with a percentage of 34.4%, is in the negative category. The acceptance aspect, with a percentage of 63.7%, was in the positive category, the response aspect, with a percentage of 42.4%, was in the positive category, the assessment aspect, with a percentage of 35.9%, was in the positive category, and the characterization aspect, with a percentage of 39.7%, was in the positive category.